Adoption of information technology in primary care physician offices in New Zealand and Denmark, Part 4: Benefits comparisons - Protti, Denis; Bowden, Tom; Johansen, Ib (Informatics in primary care, 2008)
This is the fourth in a series of five papers about the use of computing technology in general practitioner (GP) practices in Denmark and New Zealand. This paper looks at the reasons why physicians use computers with a particular emphasis on the benefits gained from automated medication prescriptions. It includes an assessment of the growth of key applications in New Zealand as well as a comparative summary of the success factors in both countries.